Analisis Yuridis Perlindungan Hukum Terhadap Konsumen Terkait Penipuan Undian Berhadiah Oleh Pelaku Usaha - Harun, Ihsanti Putri; Junus, Nirwan; Sarson, Mohammad Taufik Zulfikar (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Eventually, the public authority and society give sufficient consideration to legitimate security for buyers to shield them from misfortunes brought about by deals advancement stunts. Today, a variety of sales strategies are utilized to achieve sales goals or place a priority on increasing profits and market share, sometimes without employing an efficient sales strategy. Free giveaways, deals and sweepstakes determined to stand out to the item or business being run are instances of business entertainers' exercises, including searching for alluringly showed items at reasonable costs, handling and exercises that are beguiling purchasers. Customers suffer a lot from these and other activities. The creators of this event attempted to suggest a number of things, including: What legal measures are being taken to safeguard consumers from business actors' violations of prize promotions? Next, who is accountable for the theft of product-included promotional giveaways? The methods of normative legal research are used in this study. Subjective strategies are utilized to look at the gathered information, which are then portrayed. (1) This study concludes that government oversight and consumer protection agencies provide consumer rights violations with consumer legal protection in the form of goods sales promotion activities. Sanctions include civil law, criminal law, and sanctions if negative promotions harm customers. 2) The obligation of business actors to compensate consumers for losses resulting from product theft of promotional gifts. The following are some suggestions regarding the findings of the research: 1) Consumers, actors, consumer groups, and governments must collaborate in order for UUPK to be properly implemented in accordance with the objectives. 2) It is anticipated that prize-based promotional transactions will be more cautious for customers. 3) It is suggested that actors in business use promotions with prizes to get customers.